Internet of things-based smart facilities management services successful implementation instrument development, validity, and reliability - Sidek N.; Ali N.; Rosman R. (IEEE Computer Society, 2023)
Information systems; Information use; Instrument testing; Reliability; Terbium compounds; Content validity indices; Facilities management; Independent variables; Individual technology; Instrument development; Internal consistency reliability; Measurement instruments; Traditional approaches; Internet of things